Coupled axial tension-shear behavior of reinforced concrete walls. (15th July 2018) - Ji, Xiaodong; Cheng, Xiaowei; Xu, Mengchao
Highlights: The paper presents a series of cyclic shear tests on RC walls under tensile forces. Different axial tension force levels result in various failure modes of RC walls. Axial tension forces significantly decrease the shear strength of RC walls. The proposed formulas can estimate the effective lateral stiffness of RC walls. Design formulas of tension-shear strength of RC walls are estimated. Abstract: Reinforced concrete (RC) shear walls in high-rise buildings may experience coupled axial tension-shear loading when subjected to strong ground motions. To understand how the tensile force influences shear strength and stiffness of RC walls, a series of quasi-static tests are conducted on six wall specimens with low aspect ratios. The failure modes of the specimens vary with different degrees of axial tension forces, which include diagonal tension failure (without tensile force), shear-sliding failure (under low to moderate tensile force) and sliding failure (under high tensile force). Increase of axial tensile force leads to linear decrease of the shear strength capacity of RC walls, with a factor of approximately 0.35. Sliding shear strength of specimens subjected to high axial tension is only 24%–33% of the shear strength capacity of the specimen not subjected to axial tension. High axial tensile force also results in a significant decrease in lateral stiffness of the walls. In addition, the axial tensile behavior of RC wall specimens is also presented to validate various tension-stiffening models of cracked concrete. Finally, design formulae of shear stiffness and strength of RC walls under axial tension are estimated, using the data from this experimental program and past tests. The strut-and-tie model provides a reasonable estimate of effective lateral stiffness of low-aspect-ratio RC walls under low to moderate tensile forces. The design formulae specified in ACI 318–14 (U.S.) code provide a conservative estimate of the shear strength capacity of the RC walls subjected to tensile forces. The average experimental-to-calculated ratio is 1.68. However, the JGJ 3–2010 formulae (China) tend to overestimate the shear strength capacity of RC walls under moderate axial tensile forces, with an average experimental-to-calculated ratio of 0.93.